Potential virus vectors in stone fruit trees in Aguascalientes, Zacatecas and northern Jalisco, Mexico - Velásquez-Valle, Rodolfo; Amador-Ramírez, Mario Domingo; Medina-García, Guillermo (Revista Mexicana de Ciencias Agrícolas, 2018)
The Xiphinema sp. nematode was detected in soil, while bud mites from the family Eriophyidae and potyviruses were detected in the foliage of stone fruit trees. In the state of Aguascalientes they were found in improved peach selections, in the state of Zacatecas individuals of the genus Xiphinema spp. were found in soil from one nursery and in commercial orchards of creole peach and in an isolated peach tree in Lagos de Moreno, Jalisco. Potyviruses were detected in 12 trees from improved peach selections and in the San Isidro commercial peach cultivar in theAguascalientes municipality, Aguascalientes while in Villanueva, Zacatecas they were found in selections from peach, plum and apricot domestic trees.
Keywords: plum; peach; apricot; nematodes; potyviruses; vectors